Blanking period antiarrhythmic drugs after catheter ablation for atrial fibrillation: a meta-analysis of randomized controlled trials - Chen, Gang; Li, Guangling; Zhang, Demei; Wang, Xiaomei; Guo, Xueya (Frontiers in Cardiovascular Medicine, 2023)
Background: Antiarrhythmic drugs (AADs) are widely used after catheter ablation (CA) of atrial fibrillation (AF), but no multicenter and large-scale controlled study has confirmed that they can reduce the late recurrence of AF after CA. Moreover, the length of short-term use of AADs after CA is also controversial. Methods: PubMed, Embase, Cochrane Library, CNKI, and ClinicalTrials.gov were searched until April 25, 2022. We enrolled in randomized controlled trials (RCTs) to evaluate the efficacy of blank period AADs in predicting early and late recurrence of AF. Besides, Grading of Recommendations Assessment, Development and Evaluation (GRADE) was used to assess the quality of evidence in this meta-analysis. Results: 12 RCTs with 3625 patients were included in this meta-analysis. Short-term use of AADs after AF ablation reduced the risk of early recurrence of AF compared with the no-AADs group. In the subgroup analysis of AADs use time, only drug use time of more than two months can reduce the early recurrence of AF after CA. However, compared with the no-AADs group, short-term use of AADs after CA did not reduce the late recurrence of AF. Conclusions: Short-term use of AADs (more than two months) can reduce the early recurrence but not the late recurrence of AF after CA.